2022
DOI: 10.3390/ijms23179736
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of COVID-19 Affects the Plasma Soluble Levels of the Immune Checkpoint HLA-G Molecule

Abstract: The non-classical histocompatibility antigen G (HLA-G) is an immune checkpoint molecule that has been implicated in viral disorders. We evaluated the plasma soluble HLA-G (sHLA-G) in 239 individuals, arranged in COVID-19 patients (n = 189) followed up at home or in a hospital, and in healthy controls (n = 50). Increased levels of sHLA-G were observed in COVID-19 patients irrespective of the facility care, gender, age, and the presence of comorbidities. Compared with controls, the sHLA-G levels increased as far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(68 reference statements)
1
3
0
3
Order By: Relevance
“…Regarding a putative link between HLA-G and COVID-19 infection, it has been suggested that in an early inflammatory stage, the host might produce the anti-inflammatory cytokine IL-10, which could later enhance HLA-G expression to avoid injuries [ 57 ]. These data were further extended by a positive correlation next to IL-10 with IL-6 and IL-8 in the acute phase of the SARS-CoV-2 infection [ 58 ]. Thus, HLA-G expression and/or secretion might reflect a negative feedback response to inflammatory processes during viral infections [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding a putative link between HLA-G and COVID-19 infection, it has been suggested that in an early inflammatory stage, the host might produce the anti-inflammatory cytokine IL-10, which could later enhance HLA-G expression to avoid injuries [ 57 ]. These data were further extended by a positive correlation next to IL-10 with IL-6 and IL-8 in the acute phase of the SARS-CoV-2 infection [ 58 ]. Thus, HLA-G expression and/or secretion might reflect a negative feedback response to inflammatory processes during viral infections [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another clinical study in Korea reported that increased levels of sCD27, sCD40, sCD152, soluble cytotoxic T-lymphocyte-associated protein 4 (sCTLA-4), and sTIM3 were significantly higher in COVID-19 patients who died than in survivors ( 11 ). Moreover, in independent studies that included COVID-19 patients with severe to critical disease, increased levels of specific sICPs, such as the non-classic histocompatibility antigen G (HLA-G), sCD279, soluble programmed cell death 1 (sPD-1), soluble programmed cell death-ligand 1 (sPDL1), sTIM-3, and soluble CD137 (sCD137) ( 12 18 ) were found in peripheral blood. However, to determine whether sICPs can function as potential blood biomarkers and therapeutic targets in COVID-19, more studies are necessary to better understand their immunomodulatory behavior in the pathophysiology of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…A tempestade de citocinas tem sido responsabilizada por esses eventos [263]- [265], no entanto, muito ainda precisa ser compreendido, e vários grupos continuam a descrever outros efeitos adversos e importantes induzidos pelo SARS-CoV-2, no homem. Nesse contexto, nosso grupo de pesquisa tem contribuído substancialmente, tendo já publicado artigos sobre a participação do TREM-1 [72], [74], HLA-G [71], hormônios sexuais [73], e dos eicosanoides e acetilcolina [99]. Nesse último, mostramos que tanto sistemicamente como nos pulmões, além de citocinas, há aumento significativo de eicosanoides e ACh, cujas alterações se relacionam com mudanças da expressão genica de enzimas e de receptores, relacionados à síntese ou ação desses compostos [99].…”
Section: Resultados | 99unclassified
“…Para a análise estatística 71 Esta análise foi realizada utilizando os testes Kruskal-Wallis, Mann-Whitney, Spearman's correlation, ou Chi-square (χ2).…”
Section: Análises Estatísticasunclassified
See 1 more Smart Citation